Effectiveness and Safety Test of Antiaging Serum Combination of Ceremai Fruit (Phyllantus acidus) and Watermelon Rind (Citrullus lanatus) In Vivo - Eneng Elda Ernawati; Nani Suryani; Akmal Sodik; Farhan Hidayat Maulana; Arini Khaerunisa; Dhyneu Dwi Jayantie (JSFK (Jurnal Sains Farmasi & Klinis), 2025)
Antiaging serum is a cosmetic to prevent skin damage due to aging factors. The antiaging serum from the combination of ceremai fruit extract (Phylanthus acidus) and watermelon peel (Citrullus lanatus) has been tested ad an antioxidant, antihyperpigmentation and anti-wrinkle activities. However, its efficacy, safety, and toxicity had not yet been tested in vivo. This study aimed to evaluate these parameters using four groups of rats over four weeks. Two formulations (F1 and F2) contained the combination of ceremai fruit extract and watermelon peel, while the negative control (NC) used only the base serum, and the positive control (PC) contained a known antiaging compound. Results showed that all formulations affected moisture content, pigmentation, collagen, and skin elasticity. Notably, F2 demonstrated the most effective outcomes: it increased skin moisture by 11.2%, improved elasticity by 10.6%, enhanced collagen levels by 14.7%, and reduced pigmentation by 21.1%, without stimulating excess sebum. These results were significantly different from the negative control (p < 0.05). In addition, the results of the F2 serum toxicity test showed no toxic symptoms to the test animals because there was no irritation